Body Mass Index and Prognosis of Patients With Stage II/III Gastric Cancer After Curative Gastrectomy: Completion of Perioperative Adjuvant Chemotherapy May Be a Confounding Factor - Peng, Wei; Dai, Jing; Liu, Chao-chan; Liu, Dian; Xiao, Hua (Frontiers in Oncology, 2022)
Objective: To investigate the association between body mass index (BMI) and overall survival (OS) of patients with stage II/III gastric cancer (GC) after radical gastrectomy, and evaluate the potential influence of perioperative adjuvant chemotherapy (PAC). Methods: Medical records of 2,510 consecutive stage II/III GC patients who underwent curative resection between November 2010 and December 2020 were retrospectively reviewed. The optimal cutoff value of BMI for OS was determined by X-tile. The independent predictive factors for completeness of PAC were identified using univariate and multivariate logistic regression analyses. Cox regression analyses assessed the association among BMI, completeness of PAC, and OS. Results: Of the 2,510 patients, 813 cases with BMI < 20.3 kg/m2 were classified as belonging in the low BMI group. Further analyses confirmed that low BMI was an independent predictor for incomplete PAC (< 6 cycles, n = 920) and poorer OS (hazard ratio: 1.317, 95% confidence interval: 1.162-1.494, P < 0.001), but neo-adjuvant chemotherapy (NAC) was a protective factor. An additive effect was found in those with both low BMI and incomplete PAC, as they had even worse OS. However, in patients with low BMI, completion of PAC (≥ 6 cycles) significantly improved OS, which became comparable to that in the high BMI group (P = 0.143). Conclusions: Low preoperative BMI independently affects completion of PAC and prognosis of patients with stage II/III GC, but completing PAC can compensate for the adverse influence of low BMI on OS. Thus, strategies designed to ensure the completion of PAC, such as NAC and nutritional support, should be further investigated.